Knowledge Management Enablers and Faculty’s Knowledge Sharing Behavior in Academic Institutions of Nepal - Poudel, Bishwash Raj (Janapriya Journal of Interdisciplinary Studies, 2021)
Uncovering the factors that propel knowledge sharing behavior of faculty members in the context of Nepal shall have some practical implication. First it is a high time to move forward the discourse of implementing formalized knowledge management system in Nepal. For this, the study has identified training and development, monetary reward system, trust as significant predictors of knowledge sharing behavior. Moreover, it is a bitter paradox of knowing and not doing. There exists knowing-internalizing-doing-being gap in knowledge management context of Nepal. The core job responsibilities of faculty members may be redefined in the contemporary period where academicians have to transform their students from knowing to doing to being state of excellence.